2021
DOI: 10.2147/ccid.s310487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV Induced-Photoaging on the Hair Follicle Cycle of C57BL6/J Mice

Abstract: Purpose: To study the changes in the hair follicle cycle and related stem cells induced by photoaging to establish a mouse model of senescence in hair follicles. Methods: There were 54 C57BL6/J mice randomly divided into three groups. The UVA group and the UVB group underwent photoaging induced by UV lamps for 8 weeks. Changes in skin and the hair follicle cycle were compared by physical signs, dermoscopy, and hematoxylin and eosin and Masson's staining in each group. Western blot, immunohistochemistry, and RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Earlier, similar results have been reported on exposure of depilated C57BL/6 to UVA exposure. 53 Also, statistically significant difference ( p < 0.01) was observed between NC vs. V groups with respect to mean number of hair follicles/2400 μm (for each skin sample, hair follicle/2400 μm at five random places in the sample was tabulated) (Fig. 4A4).…”
Section: 7mentioning
confidence: 89%
“…Earlier, similar results have been reported on exposure of depilated C57BL/6 to UVA exposure. 53 Also, statistically significant difference ( p < 0.01) was observed between NC vs. V groups with respect to mean number of hair follicles/2400 μm (for each skin sample, hair follicle/2400 μm at five random places in the sample was tabulated) (Fig. 4A4).…”
Section: 7mentioning
confidence: 89%
“…It is well established that HFs provide an immune‐privileged environment, which is an important factor for maintaining host immune cells in the skin 53 . This process is also considered crucial for maintaining the bulge in HFs, where epithelial HF stem cells reside 54,55 . Similarly, HF‐maintained immune privilege is also important to suppressing immune‐mediated inflammation 56 .…”
Section: Discussionmentioning
confidence: 99%
“…53 This process is also considered crucial for maintaining the bulge in HFs, where epithelial HF stem cells reside. 54,55 Simi-larly, HF-maintained immune privilege is also important to suppressing immune-mediated inflammation. 56 Therefore, here, we first defined the pathogenesis of arsenicals in shaved haired Ptch1 +/-/C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation is the dominant factor in extrinsic aging and can result in hyperpigmentation, wrinkled skin, increased roughness, and loss of elasticity [ 3 ]. Previous studies indicated that chronic exposure to UVB radiation could induce skin damage by increasing the levels of reactive oxygen species (ROS) and eventually cause characteristic symptoms of skin photoaging, such as hyperplasia of sebaceous glands, deeper and wider wrinkle formation, and reduction in skin elasticity [ 4 7 ]. Moreover, there is clear evidence that the development of benign and malignant neoplasms is increased on photoaged skin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%